2003
DOI: 10.1109/taes.2003.1188899
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of aircraft container loading

Abstract: We address the problem of loading as much freight as possible in an aircraft while balancing the load in order to minimize fuel consumption and to satisfy stability/safety requirements. Our formulation methodology permits to solve the problem on a PC, within ten min, by off-the-shelf integer linear programming software. This method decides which containers to load (and in which compartment) and which to leave on the ground.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 11 publications
1
46
1
6
Order By: Relevance
“…In the field of ULD location problems, the papers by Mongeau and Be`s (2003) and Souffriau et al (2008) are the closest to our work. Even if this is not their first goal, they consider the ULD locations in the aircraft and their impact on the CG.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the field of ULD location problems, the papers by Mongeau and Be`s (2003) and Souffriau et al (2008) are the closest to our work. Even if this is not their first goal, they consider the ULD locations in the aircraft and their impact on the CG.…”
Section: Introductionsupporting
confidence: 56%
“…Other papers deal with passengers (see eg Tian et al, 2008), bulk freight (see eg Amiouny et al, 1992) or military items with specific properties. Finally, Mongeau and Be`s (2003) and Souffriau et al (2008) propose exact methods, whereas all other papers we have examined describe heuristics (see eg Fok and Chun, 2004). However, these two papers differ from our work on two important aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Meller ''Although these formulations provide valuable insight on the CLP (see [20][21][22][23][24][25]), they assumed that both a set of cartons with known dimensions and the quantities of products are given. The models then select a number of cartons to pack a given set of products.…”
Section: Current Sizing Methodsmentioning
confidence: 99%
“…A further extension of this work was Mathur (1998), which provided an algorithm with a better worst-case performance. A simple greedy heuristics for balancing was proposed in Amiouny et al (1992); a military application for loading air cargo was suggested in Ng (1992); and maximizing air freight loading while balancing the weight to minimize fuel consumption and satisfy stability and safety requirements was studied in Mongeau and Be`s (2003). Only one paper, by Huang and Chi (2007), deals with the air cargo consolidation problem for air freight forwarders, developing a heuristic algorithm to solve the problem by using a Lagrangian relaxation.…”
Section: Introductionmentioning
confidence: 99%